Strategic business transformation : the 7 deadly sins to overcome - 222046 Nair, Mohan (Hoboken, N.J. : Wiley, 2011)
"A solid framework for businesses to create a market-developing strategyBusiness transformation is a key executive management initiative that attempts to align people, process, and technology initiatives of an organization more closely with its business strategy and vision to support and help innovate new business strategies and meet long-term objectives. Strategic Business Transformation reveals how you can predict if your market is transforming, linking and aligning ten key strategic variables under a common strategic dashboard. Provides a tested framework of this strategic invention and transformation that the author has applied to several companies Includes case studies of the entrepreneurial and large multi-billion revenue institutions that have used this method?and succeeded Shows how internal and external factors drive should drive strategic transformation Filled with case studies and practical examples, this book gives readers a proven framework from which to create a transformative business strategy"--